2020
DOI: 10.3892/ijmm.2020.4537
|View full text |Cite
|
Sign up to set email alerts
|

Muscle metabolomics analysis reveals potential biomarkers of exercise‑dependent improvement of the diaphragm function in chronic obstructive pulmonary disease

Abstract: decreased diaphragm function is a crucial factor leading to reduced ventilatory efficiency and worsening of quality of life in chronic obstructive pulmonary disease (cOPd). Exercise training has been demonstrated to effectively improve the function of the diaphragm. However, the mechanism of this process has not been identified. The emergence of metabolomics has allowed the exploration of new ideas. The present study aimed to analyze the potential biomarkers of exercise-dependent enhancement of diaphragm funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 112 publications
1
10
0
Order By: Relevance
“…This causes irisin release, thereby promoting the browning of beige fat cells in white adipose tissue, enhanced thermogenesis, increased energy expenditure, and maintenance of glucose homeostasis 42 , 43 . The increase of threonine levels in vivo in the intervention group could be partially responsible for these beneficial effects; however, further studies are warranted 44 . Similarly, the increase of tyrosine levels as observed from the metabolomic and pathway analysis (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…This causes irisin release, thereby promoting the browning of beige fat cells in white adipose tissue, enhanced thermogenesis, increased energy expenditure, and maintenance of glucose homeostasis 42 , 43 . The increase of threonine levels in vivo in the intervention group could be partially responsible for these beneficial effects; however, further studies are warranted 44 . Similarly, the increase of tyrosine levels as observed from the metabolomic and pathway analysis (Fig.…”
Section: Discussionmentioning
confidence: 96%
“… Vieira Ramos et al (2018) conducted treadmill aerobic training on mice with COPD and found that it improved the antioxidant capacity of the diaphragm. Li et al (2020) found that after aerobic exercise in water, the nicotinic acid metabolism level in the diaphragm of COPD rats was upregulated, thus protecting the diaphragm and ventilatory muscle from oxidative damage and improving diaphragm muscle strength and ventilatory function. However, this experiment did not directly detect oxidative stress indicators.…”
Section: Effect and Mechanism Of Exercise On Oxidative Stress Of The Diaphragm In Copdmentioning
confidence: 97%
“…Aerobic exercise is a cornerstone of pulmonary rehabilitation(PR) to improve health-related quality of life and exercise capacity, as well as reduce dyspnea, hospitalization, exacerbation, and mortality 9,10,11 . Some studies suggest that exercises can reduce chronic in ammation, improve the diaphragm and cognitive function, and reverse airway remodeling 12,13,14,15 . However, despite exercise's profound bene ts for treating COPD, knowledge of how exercise improves health and the molecular mechanism of immunometabolism response to exercise remains limited 43,45 .…”
Section: Introductionmentioning
confidence: 99%